Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap TaxAvoidance pada Perusahaan UKM di Surabaya dan Sidoarjo Periode Tahun 2017-2019 - Saputra, Marga; Tjahjono, Endro; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThis study was conducted to analyze the effect of Good Corporate Governance (Board of Director’s Size and Managerial Ownership), and Company Size toward Tax Avoidance of Small and Medium Enterprises (SMEs) in Surabaya and Sidoarjo in 2017-2019 period.The sampling technique was purposive sampling in Small and Medium Enterprises (SMEs). Therefore, 11 companies were obtained and it gained 33 samples of observational data during three years of research period. Multiple linear regression method analysis is used to analyze these data.Hence, the feasibility of the study model has shown that Tax Avoidance was significantly influenced by the Board of Directors, Managerial Ownership, and Company Size. This showed that the independent variable is able to explain the diversity of Tax Avoidance. Afterward, the result of hypothesis testing proved that; 1) Board of Directors’ Size has a positive and significant effect on Tax Avoidance; 2) Managerial Ownership has a positive and significant effect on Tax Avoidance; 3) Company Size has no significant effect on Tax Avoidance. According to the authors, it is because of companies that have been registered and had legal standing. They have an obligation to pay taxes based on the company’s proportion.Based on the research model has been proposed by the author. It indicated the variation of Tax Avoidance variables can be explained together with by Board Directors size’ ratio, Managerial Ownership, and Company Size variables in the amount of 26,5%. Whereas, its remaining in the amount of 73,5% was influenced by variables outside the research, for instance; Leverage variables, Liquidity, CSR and etc.Keywords : Board of Directors Size, Managerial Ownership, Company Size, Tax Avoidance